2004
DOI: 10.1242/dev.01003
|View full text |Cite
|
Sign up to set email alerts
|

polyhomeoticis required for somatic cell proliferation and differentiation during ovarian follicle formation inDrosophila

Abstract: The polyhomeotic (ph) gene of Drosophila is a member of the Polycomb group (Pc-G) genes, which are required for maintenance of a repressed state of homeotic gene transcription, which stabilizes cell identity throughout development. The ph gene was recovered in the course of a gain-of-function screen aimed at identifying genes with a role during ovarian follicle formation in Drosophila, a process that involves coordinated proliferation and differentiation of two cell lineages, somatic and germline. Subsequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
3
19
0
1
Order By: Relevance
“…Failure to adjust these two processes leads to 16-cell cyst packaging defects that manifest as compound egg chambers. These rare phenotypes had previously only been described upon perturbation of some signaling pathways, such as Notch, or Polycomb regulation (Jackson and Blochlinger, 1997;Narbonne et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Failure to adjust these two processes leads to 16-cell cyst packaging defects that manifest as compound egg chambers. These rare phenotypes had previously only been described upon perturbation of some signaling pathways, such as Notch, or Polycomb regulation (Jackson and Blochlinger, 1997;Narbonne et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…It was recently reported that the adult Drosophila midgut undergoes rapid cell turnover, similarly to the vertebrate intestine, and the fundamental similarities between Drosophila and vertebrate intestines have been revealed (Micchelli & Perrimon 2006;Ohlstein & Sparding 2006). The reproductive system is characterized by a high cellular proliferation rate (Narbonne et al 2004). Therefore, the need for DRE in dANT promoter activity in the gut as well as in reproductive systems may be associated with the cell-proliferation of these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the importance of tissue specificity. Indeed, many studies have shown genetically that the PcG and TrxG genes have tissue-specific roles (Breen, 1999;Chanas and Maschat, 2005;Janody et al, 2004;Narbonne et al, 2004). It may well be that each type of adult stem cell in Drosophila uses a different set of PRE/TREs.…”
Section: Switching Upon Differentiation: Insights From Fliesmentioning
confidence: 99%